From ambition to action: how to achieve integration in omni-channel? - Mirzabeiki, Vahid; Saghiri, Soroosh Sam (Elsevier, 2020)
The paper aims to identify how companies can enhance their omni-channel activities through improved data management and integration. Multiple case studies of ten leading UK companies are conducted by using multiple sources of data, including interviews, archival documents and expert focus groups. The case companies are manufacturers and retailers in the clothing, food, and Fast-Moving Consumer Goods (FMCG) sectors. A thorough list of challenges in the implementation of omni-channel systems is generated and a number of propositions on enablers and barriers to omni-channel data integration are recommended. Our findings emphasise the importance of automating and standardising data capturing and sharing methods, and centralising data storage among companies and channels, which lead to improved efficiencies. They also indicate that omni-channel systems should be responsive to the choices of customers, and integration of the information systems of logistics service providers and their buyers is crucial in making omni-channels more efficient and consumer-responsive.
Keywords: Omni-channel; Integration; Data management; Enablers; Barriers